2014
DOI: 10.1016/j.aop.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Scattering and bound states of fermions in a mixed vector–scalar smooth step potential

Abstract: The scattering of a fermion in the background of a smooth step potential is considered with a general mixing of vector and scalar Lorentz structures with the scalar coupling stronger than or equal to the vector coupling. Charge-conjugation and chiralconjugation transformations are discussed and it is shown that a finite set of intrinsically relativistic bound-state solutions appears as poles of the transmission amplitude. It is also shown that those bound solutions disappear asymptotically as one approaches th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 117 publications
0
24
0
Order By: Relevance
“…Considering mixed scalar-vector potentials the Dirac equation in (1+1) dimensions have been investigated for a sign potential [17] and smooth step potential [18]. In the context of mixed scalar-vector-pseudoscalar potentials (the most general Lorentz structure), the bound-state solutions for fermions and antifermions in (1+1) dimensions have been studied for harmonic oscillator potential [19], Pöschl-Teller potential [20], Cornell potential [21,22] and Coulomb potential [23].…”
Section: Introductionmentioning
confidence: 99%
“…Considering mixed scalar-vector potentials the Dirac equation in (1+1) dimensions have been investigated for a sign potential [17] and smooth step potential [18]. In the context of mixed scalar-vector-pseudoscalar potentials (the most general Lorentz structure), the bound-state solutions for fermions and antifermions in (1+1) dimensions have been studied for harmonic oscillator potential [19], Pöschl-Teller potential [20], Cornell potential [21,22] and Coulomb potential [23].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [13] and [14], it has been shown that the Dirac equation with a scalar potential plus a time component of vector potential of the same functional form is manageable if the vector coupling does not exceed the scalar coupling, and that the bound states for mixed scalar-vector potentials with the kink-like profiles sgn x and tanh x/λ are intrinsically relativistic solutions. Furthermore, it has been shown that the fermion can be confined in a highly localized region of space under a very strong field without any chance for spontaneous pair production related to Klein's paradox.…”
Section: Introductionmentioning
confidence: 99%
“…The complete set of solutions for massive fermions under the influence of a kink-like scalar potential added by the time component of a vector potential with the same functional form was considered in Refs. [13] and [14], in Ref. [13] for the background field behaving like sgn x, and in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations